Highly Stable and Antibacterial Two‐Dimensional Tungsten Disulfide Lamellar Membrane for Water Filtration. Issue 1 (20th December 2018) - Cheng, Peng; Chen, Yan; Yan, Xi; Wang, Yanjie; Lang, Wan‐Zhong
Abstract: Two‐dimensional (2D) lamellar membranes consisting of restacked WS2 nanosheets have shown excellent separation properties for water filtration. The stability, antifouling properties, and antibacterial activities of the WS2 laminar membranes were investigated for practical application. We discovered that the separation properties of the WS2 laminar membranes changed slightly after soaking in water for 28 days as well as that of a 45 h‐cross‐flow filtration, demonstrating an extraordinary operational stability of the WS2 laminar membranes. The remarkable stability is related to the dominant van der Waals interactions between WS2 nanosheets. In addition, the WS2 laminar membranes exhibited excellent antibacterial properties against S. aureus and E. coli with antibacterial rates of 91.3 % and 89.7 %, respectively. These properties of the WS2 laminar membranes make them promising candidates for application in water filtration. Abstract : Stable and antibacterial membranes ! Laminar WS2 membranes possess excellent stability in water and ethanol even during a 45 h‐cross‐flow filtration. The antibacterial rates of the WS2 membranes against S. aureus and E. coli are as high as 91.3 % and 89.7 %, respectively.